1976
DOI: 10.1007/bf01868883
|View full text |Cite
|
Sign up to set email alerts
|

The use of ionophores of rapid loading of human red cells with radioactive cations for cation-pump studies

Abstract: Techniques are described for the rapid loading of intact human red cells with radioactive isotopes of alkali cations or Ca2+ by using ionophorous compounds (nigericin, gramicidin D and A 23187). Loading was rapid and efficient if the membrane potential of the cells was rendered more negative inside. After cation loading the ionophores could be bound to albumin and removed by repeated washings. The ATP and 2,3-DPG contents of the cells were practically unaltered by this treatment. Passive membrane permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(30 citation statements)
references
References 26 publications
4
25
1
Order By: Relevance
“…However, the initial K ϩ efflux, which occurs before there is substantial cell lysis, is likely to cause the extensive volume reduction seen in the early phases of HlyA-induced hemolysis. This resembles what has been observed with Ca 2ϩ ionophores (17,24). A good candidate for an activated K ϩ efflux pathway is the K Ca 3.1 channel (SK 4 or Gardos channel); the only Ca 2ϩ -activated K ϩ channel known to be present in erythrocytes (25,26).…”
Section: Discussionsupporting
confidence: 87%
“…However, the initial K ϩ efflux, which occurs before there is substantial cell lysis, is likely to cause the extensive volume reduction seen in the early phases of HlyA-induced hemolysis. This resembles what has been observed with Ca 2ϩ ionophores (17,24). A good candidate for an activated K ϩ efflux pathway is the K Ca 3.1 channel (SK 4 or Gardos channel); the only Ca 2ϩ -activated K ϩ channel known to be present in erythrocytes (25,26).…”
Section: Discussionsupporting
confidence: 87%
“…It is apparent that A23187-induced cyclic GMP production is less in the presence of SOD or SOD and CAT than in their absence (cf Table 5 and Figure 4). This may well reflect protein binding of the ionophore, as A23187 is known to bind to albumin: indeed binding of A23187 to albumin has been used as a technique for rapid removal and reversal of the effects of A23187 (Sarkadi et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Trapped PBS was estimated by tagging the solution with '"IHSA (0.15 MCi/ml). The water content was estimated by drying the sample at 1050C to a constant weight (generally within [24][25][26][27][28][29][30][31][32][33][34][35][36] h). This value was corrected for the trapped PBS solution.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretically, PTH may also promote calcium entry into RBC, and it has been shown that small increases in intracellular calcium of RBC evoked crenation and increased rigidity (20)(21)(22)(23)(24). Thus, excess blood levels of PTH in patients with uremia could be, at least in part, responsible for the reduced survival of RBC in these patients.…”
mentioning
confidence: 99%